Visual merchandising: A bibliometric analysis and future research proposals - Batista, Karen; Martins, Ingrid de Matos; Limongi, Ricardo (Contextus - Revista Contemporânea de Economia e Gestão, 2020)
This work aimed to investigate the studies on visual merchandising in theoretical, methodological and empirical aspects. Bibliometric research was carried out based on 35 articles published in journals. The analyzes present the number of articles per year, main journals, most cited references, most used keywords, in addition to the methodology, considering the approach, research method, data collection and analysis technique. It was possible to conclude that the theme is relatively new, justifying an opportunity for future research. In this sense, a research agenda is proposed with three possible paths to be followed by future studies, namely: studies with a qualitative approach, comparison between different countries and comparison between sectors and intersector.